The sin of certainty : why God desires our trust more than our "correct" beliefs - Enns, Peter, 1961- (New York, NY : HarperOne, an imprint of HarperCollins Publishers, 2016)
Enns offers a model of vibrant faith that views skepticism not as a loss of belief, but as an opportunity to deepen religious conviction with courage and confidence. He models an acceptance of mystery and paradox and shows that God prefers this path because it is only this way by which we can become mature disciples who truly trust God. In doing so, he gives Christians who have known only the demand for certainty permission to view faith on their own flawed, uncertain, yet heartfelt, terms.
I don't know what I believe anymore -- How we got into this mess -- "You abandoned me, God; you lied" (and other Bible lessons) -- Two miserable people worth listening to -- Believing in God: so easy even a demon can do it -- Uh-oh: when certainty is caught off guard (and why that might not be such a bad idea) -- God wants you dead -- Cultivating a habit of trust -- Beyond trust.
Includes index.
Includes bibliographical references (pages [217]-228) and index.
Keywords: Faith; Trust in God -- Christianity; Truth -- Religious aspects -- Christianity